Edukasi latihan kombinasi pliometrik dan peregangan terisolasi aktif untuk meningkatkan fleksibilitas otot tubuh - Raminda, Santri; Fadhail, Maulana Ahsan; Aliun, Fatimah Wahab; Kurniawan, Ryanda Masri; Zulfikar, Zulfikar (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Flexibility is an important component of daily activities. Physical activity, including movements involving jumping, can stimulate the brain and increase blood flow to the brain, which in turn can support cognitive function and help slow memory decline. Active and repetitive muscle stretching for short durations, while plyometrics involve explosive movements to increase strength and agility. Physical exercises such as plyometrics can increase circulating BDNF concentrations, thereby inducing brain plasticity and cognitive enhancement. Physical exercise may support the release of neurotransmitters and neurotrophins in an activity-dependent manner. Increasing flexibility will reduce pain, and increase range of motion without causing excessive strain or injury. Purpose: Providing knowledge about maintaining flexibility of body muscle movement with a combination of plyometric exercises and active isolation stretching. Method: This activity was carried out at the Siger Physio Way Halim Bandar Lampung Clinic in January 2025. With quota sampling, 22 teenagers were selected as respondents. Participants were given instructions by instructors in doing the exercises and then carried out direct practice. Active isolated stretching actions are by holding each stretching movement for 2-3 seconds and repeated up to 8 times, then performing plyometric movements in the form of jumping in place, box jumps and high jumps. Results: Found that the majority of respondents were aged 18-22 years, namely 11 (50.0%). While the profession of the type of sport pursued was football as many as 8 (36.4%), Badminton as many as 4 (18.2%), Basketball as many as 6 (27.2%), and athletics as many as 4 (18.2%). Getting the respondent's jump distance in the pre-test with a mean value of 34.2 cm and a standard deviation of ± 5.66, while in the post-test with a mean value of 37.4 and a standard deviation of ± 4.92. Conclusion: Providing education and training in combination of active isolated stretching with plyometrics is quite effective and can improve understanding in maintaining body muscle flexibility and avoiding the risk of injury. Suggestion: It is expected to conduct further research and develop research with more specific factors to provide knowledge of the importance of carrying out muscle stretching actions as an effort to maintain flexibility and avoid the risk of injury. Keywords: Combination exercise; Flexibility; Muscle stretching; Risk of injury Pendahuluan: Fleksibilitas merupakan komponen yang penting dalam beraktivitas sehari-hari. Aktivitas fisik, termasuk gerakan yang melibatkan melompat, dapat merangsang otak dan meningkatkan aliran darah ke otak, yang pada gilirannya dapat mendukung fungsi kognitif dan membantu memperlambat penurunan daya ingat. Peregangan otot secara aktif dan berulang dengan durasi singkat, sementara pliometrik melibatkan gerakan eksplosif untuk meningkatkan kekuatan dan kelincahan. Latihan fisik seperti plyometric dapat meningkatkan konsentrasi BDNF dalam sirkulasi, sehingga menginduksi plastisitas otak dan peningkatan kognitif. Latihan fisik mungkin mendukung pelepasan neurotransmiter dan neurotropin dengan cara yang bergantung pada aktivitas. Dengan meningkatnya fleksibilitas akan mengurangi nyeri, dan meningkatkan jangkauan gerak tanpa menyebabkan ketegangan berlebihan atau cedera. Tujuan: Memberikan pengetahuan tentang menjaga fleksibilitas gerak otot tubuh dengan latihan kombinasi pliometrik dan peregangan isolasi aktif. Metode: Kegiatan ini dilaksanakan di Klinik Siger Fisio Way Halim Bandar lampung pada bulan Januari 2025. Dengan quota sampling mendapatkan 22 remaja yang menjadi responden. Para peserta diberikan petunjuk dengan instruktur dalam melakukan latihan dan selanjutnya melakukan praktik langsung. Tindakan peregangan terisolasi aktif yaitu dengan menahan setiap gerakan peregangan selama 2-3 detik dan diulangi hingga 8 kali, selanjutnya melakukan gerakan pliometrik berupa lompat di tempat, lompat kotak dan lompat tinggi. Hasil: Mendapatkan bahwa usia responden sebagian besar di usia 18 – 22 tahun yaitu sebanyak 11(50.0%). Sedangkan profesi jenis olah raga yang ditekuni adalah sepak bola sebanyak 8 (36.4%), Bulutangkis sebanyak 4(18.2%), Bola basket sebanyak 6(27.2%), dan atletik sebanyak 4(18.2%). Mendapatkan jarak lompatan responden pada pre-test dengan nilai mean 34.2 cm dan standar deviasi ±5.66, sedangkan pada post-test dengan nilai mean 37.4 dan standar deviasi ±4.92. Simpulan: Pemberian edukasi dan latihan kombinasi peregangan terisolasi aktif dengan pliometrik cukup efektif dan dapat meningkatkan pemahaman dalam menjaga fleksibilitas otot tubuh dan menghindari risiko cedera. Saran: Diharapkan untuk dilakukan penelitian lanjutan dan mengembangkan penelitian dengan faktor yang lebih spesifik untuk memberikan pengetahuan pentingnya melakukan tindakan peregangan otot sebagai upaya menjaga fleksibilitas dan menghindari risiko cedera.